Epigenetic Modifications in Pediatric Acute Lymphoblastic Leukemia - Burke, Michael J.; Bhatla, Teena (Frontiers in Pediatrics, 2014)
Aberrant epigenetic modifications are well-recognized drivers for oncogenesis. Pediatric acute lymphoblastic leukemia (ALL) is no exception and serves as a model toward the significant impact these heritable alterations can have in leukemogenesis. In this brief review, we will focus on the main aspects of epigenetics which control leukemogenesis in pediatric ALL, mainly DNA methylation, histone modification and microRNA alterations. As we continue to gain better understanding of the driving mechanisms for pediatric ALL at both diagnosis and relapse, therapeutic interventions directed toward these pathways and mechanisms can be harnessed and introduced into clinical trials for pediatric ALL.